Associations between women’s bargaining power and the adoption of rust-resistant wheat varieties in Ethiopia - Euler, Michael; Jaleta, Moti; Gartaula, Hom (Elsevier, 2024)
The dynamics in intra-household decision-making are often neglected in literature on the adoption of agricultural innovations. However, households’ farm management decisions are often made following negotiations between female and male farmers. These may differ in terms of individual bargaining power and personal preferences. A better understanding of the links between gender roles in household decision-making and the adoption of technologies is postulated to enhance the uptake of innovations in smallholder farming systems. In this study, we use survey data from 1,088 wheat-producing households in Ethiopia to analyze the links between women’s role in household decisions concerning crop production and the adoption and turnover rates of rust-resistant wheat varieties. We interviewed female and male respondents from the same households, but separately, which facilitated capturing individual perceptions and the intra-household dynamics in decision-making. To account for observed heterogeneity that may simultaneously determine the level of women’s agency and varietal adoption by households, we employed Inverse Probability-Weighted Regression Adjustment (IPWRA). A positive association was found between women’s role in decision-making concerning choice of wheat seed and household adoption of rust-resistant wheat varieties and wheat varietal turnover. Spouses may be in agreement or have different opinions regarding their decision-making roles. The disagreement scenario in which the wife claims to have a role in decision-making is associated with lower adoption rates of rust-resistant wheat varieties and less frequent testing of new varties in recent growing seasons, compared to a scenario where both spouses agree that wives do not have a role. We conclude that gender-disaggregated data and the examination of intra-household decision-making can offer novel and valuable insights for designing and implementing strategies to enhance the uptake of agricultural technologies among smallholders. The results emphasize the need to include complementary perspectives on the intra-household decision-making process.